Maintaining Access to print Materials – a Finnish Model - Vattulainen, Pentti (LIBER Quarterly: The Journal of the Association of European Research Libraries, 2005)
Even though there are signs that the end of the hybrid library might well be in sight within a few years, we still have to manage and develop the hybrid library. Hybridism manifests itself in all sectors of the library profession, starting from library space and building planning, information provision on internet, virtual reference etc. In collection management one of the most challenging issues is how to manage the rising costs of hybrid collection development. The challenge is to provide access for every user to the document he or she needs and at same time to ensure at least an acceptable basic print collection in the library (Ceynova & Coners, 2003). Many tools have been developed to support local libraries in managing hybridism. Co-operation and specialisation of different types of libraries is naturally needed in this. Another direction is to provide centralised tools for managing reasonable service levels for users in terms of access to information. In Finland, library co-operation has been developed over many decades and specialisation in terms of collections and database constructions etc. have been essential in formulating national collections.